2021
DOI: 10.1542/hpeds.2020-003418
|View full text |Cite
|
Sign up to set email alerts
|

One Call Away: Addressing a Safety Gap for Urgent Issues Post Discharge

Abstract: OBJECTIVES: The transition period from hospitalization to outpatient care can be high risk for pediatric patients. Our aim was to profile the use of a “safety net” for families through provision of specific inpatient provider contact information for urgent issues post discharge. METHODS: In this prospective study, we implemented an updated after-visit summary that directed families to call the hospital operator and specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A healthcare provider's responsibility to care for children does not end upon hospital discharge, and interventions are not provided in certain settings only. The transition from hospital to home is a particularly high‐risk factor for paediatric patient safety (Yale et al., 2021); however, this study did not identify digital health interventions related to post‐discharge care. These findings suggest the need to develop interventions to maintain nursing continuity during the hospital‐to‐home transition.…”
Section: Discussionmentioning
confidence: 84%
“…A healthcare provider's responsibility to care for children does not end upon hospital discharge, and interventions are not provided in certain settings only. The transition from hospital to home is a particularly high‐risk factor for paediatric patient safety (Yale et al., 2021); however, this study did not identify digital health interventions related to post‐discharge care. These findings suggest the need to develop interventions to maintain nursing continuity during the hospital‐to‐home transition.…”
Section: Discussionmentioning
confidence: 84%
“…It can lead to postdischarge issues such as missed follow-up appointments, medication errors, and failure to activate contingency plans. [1][2][3][4][5] To mitigate these safety risks, many evidence-based and patient-centered discharge transition bundles have been developed, with most supporting the use of postdischarge phone calls (PDPCs) as adjunct safety tools and a component of complete hospital-to-home care. [6][7][8][9] Several studies have demonstrated the potential benefit of the PDPC in the early detection of postdischarge issues.…”
Section: Introductionmentioning
confidence: 99%